The putative Cationic Amino Acid Transporter 9 is targeted to vesicles and may be involved in plant amino acid homeostasis - Yang, Huaiyu; Stierhof, York-Dieter; Ludewig, Uwe (Frontiers in Plant Science, 2015)
Amino acids are major primary metabolites. Their uptake, translocation, compartmentation and re-mobilization require a diverse set of cellular transporters. Here, the broadly expressed gene product of CATIONIC AMINO ACID TRANSPORTER 9 (CAT9) was identified as mainly localized to vesicular membranes that are involved in vacuolar trafficking, including those of the trans-Golgi network. In order to probe whether and how these compartments are involved in amino acid homeostasis, a loss-of-function cat9-1 mutant and ectopic over-expressor plants were isolated. Under restricted nitrogen supply in soil, cat9-1 showed a chlorotic phenotype, which was reversed in the over-expressors. The total soluble amino acid pools were affected in the mutants, but this was only significant under poor nitrogen supply. Upon nitrogen starvation, the major soluble amino acid leaf pools decreased. This decrease was lower in cat9-1 and augmented in the over-expressor. Over-expression generally affected total soluble amino acid concentrations and finally improved the survival upon severe nitrogen starvation. The results potentially identify a novel function of vesicular amino acid transport mediated by CAT9 in the cellular nitrogen-dependent amino acid homeostasis.